New fossil gastropod species (Mollusca: Gastropoda) from the upper Miocene of the Canary Islands (Spain) - Martín-González, Esther; Vera-Peláez, José Luis; Castillo, Carolina; Lozano-Francisco, M. Carmen (Zootaxa, 2018)
Ten new species of fossil gastropods from the upper Miocene (Tortonian) of the Canary Islands (Spain) are described. Among these are three species of the genus Patella, a group with few fossil representatives, as well as three others representing the family Trochidae. The remaining new species represent Caenogastropoda. This study improves our knowledge of the fossil malacofauna from the Miocene of these islands. Together with the Azores and Madeira archipelagos, the Canaries belong to the Macaronesian biogeographic region. The described species are indicative of rocky coastal environments, and are thus expanding the current understanding of such ecosystems and their associated marine molluscs such as the family Patellidae whose fossil record is scarce.        New species: Patella tintina Martín-González & Vera-Peláez sp. nov., Patella maxoratensis Martín-González & Vera-Peláez sp. nov., Patella mahamensis Martín-González sp. nov., Jujubinus ajachaensis Martín-González & Vera-Peláez sp. nov., Osilinus burgadoi Martín-González sp. nov., Gibbula tindayaensis Martín-González & Vera-Peláez sp. nov.,        Cerithium miocanariensis Martín-González & Vera-Peláez sp. nov., Tectarius isletaensis Vera-Peláez sp. nov., Morula mionigra Martín-González sp. nov. and Conus fuerteventurensis Vera-Peláez & Martín-González sp. nov.